Political Leadership and Racial Harmony in Local Government - Maimane, Mmusi Aloysias (My University, 2012)
This is a study on political leadership and the manner with which it seeks to create a society that is racial harmonized. Racial harmony is about development. A number of variables will examine how development takes place. This is about examining economic growth, participation of citizens in development and ultimately about sustainable growth. This study will argue that the satisfaction of human needs as a means is a quintessential part of racial harmony. This is not a study on racism although racism can be a leading symptom of a society that is without harmony. Two terms will be used interchangeably, these being ‘integration’ and ‘harmony’. Integration is seen as being the ability for races to live in common spaces; harmony is the pursuit of peace amongst different races. A further imperative in the discourse on racial harmony is about creating a legislative framework whereby redress policies can be implemented. In the research key comparisons are made between developing countries that have introduced positive discrimination policies and those who have not. The outcome is that nations who have historically experienced racism will need to have policies of this nature in place to address a legacy of inequity and discrimination. The City of Johannesburg is a microcosm of the South African society. This research interviews leaders from the City and the community. The conclusions reached are, inter alia, that corruption and service delivery were key areas of improvement in order for the City to attain a sense of racial harmony. The study is not confined to the City but undertakes to ii make comparisons with developing nations, globally and in Africa, who are dealing with the challenge of racial disharmony. Four factors emerge as central to harmony. These are economic growth, land ownership, leadership, and policy frameworks. Urban land needs to be distributed in Johannesburg to create equity and identity for residents. Economic growth is a key aspect to reduce tensions where resources are limited and competition for these increases. The current policy framework of Affirmative Action must be abandoned and an efficient process of Black Economic Empowerment models must be implemented to broaden the delivery base. Poor leadership hinders racial harmony, whilst leaders who design strategic visions and national plans become essential when nations and societies are striving to become harmonized.
MM thesis - P&DM
Keywords: Local government; Political leadership; Reconciliation